The missing middle of childhood - Maj-Lis Voss; Mariam Claeson; Sven Bremberg; Stefan Swartling Peterson; Tobias Alfvén; Grace Ndeezi (Taylor & Francis Group, 2023)
Middle childhood, between six and twelve years, is a critical bridge between earlier childhood and adolescence with rapid physical and psychological transitions. Most of the world's 2.6 billion young people, of which the middle childhood age group is a significant portion, live in low- and middle-income countries. Many live in environments that place them at high and growing risk for mental ill-health, injuries, and adoption of risky behaviours that often lead to non-communicable diseases in later years. Still, middle childhood, the 'missing middle,' is omitted from global health information systems, targeted policies, and strategies. The dearth of internationally comparable and standardised indicators on middle childhood in major international development agency databases hampers age-appropriate policy and programme development. Better understanding of the needs of this increasingly vulnerable population is critical. Middle childhood needs to be an explicit focus within child-focused research and implementation. Standardised, comprehensive, and relevant indicators are required to quantify the contribution of middle childhood to the global burden of disease and to facilitate interventions, monitoring, and evaluation, to ensure that all children flourish and thrive.